Roles, Rules, and Keys: How Different Play Configurations Shape Collaborative Science Inquiry. Issue 4 (20th October 2019) - DeLiema, David; Enyedy, Noel; Danish, Joshua A.
Abstract : Taking place within the Science Through Technology-Enhanced Play (STEP) design-based research project, this paper describes how first- and second-grade students use their bodies to imaginatively become microscopic particles inside of a collaborative simulation of state change (e.g., liquid to gas) and within two distinct play spaces: a modeling activity and a game activity. As participants at once bring play to life in the classroom and learn about microscopic particles, they introduce and enact distinct configurations of roles, rules, and keys that shape their moment-to-moment activity and their pathways through science inquiry. Participants' integration of distinct roles, rules, and keys during stretches of play foster on the one hand cycles of open-ended creation, observation, and destruction, and on the other hand generation of pragmatic strategies for winning assessed through game metrics. Overall, this paper introduces a framework for tracking the collaborative instantiation of roles, rules, and keys, provides preliminary documentation of how these characteristics shape learning, and invites reflection on how to move beyond general claims about games benefiting learning.